2020
DOI: 10.52804/ijaas2020.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting dates and sources of nitrogen on growth and yield of cauliflower at Rampur, Chitwan, Nepal

Abstract: Appropriate time of planting and use of suitable sources of nitrogen are highly conducive for better growth and yield of cauliflower. A field experiment was conducted to study the effect of planting dates and sources of nitrogen on growth & yield of cauliflower at horticulture research block of Agriculture and Forestry University, Rampur, Chitwan, Nepal from 1st Nov 2019 to 4th March 2020 using ‘Snow mystic’, a late season variety of cauliflower. The study was laid out in split-plot design with two dates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The timing of curd initiation, influenced by transplanting dates, is a crucial factor affecting yield and maturity. Ara et al (2009) [1] reported significant effects on vegetative growth parameters, such as plant height, number of leaves, whole plant weight, marketable curd weight, and yield, based on both the variety and planting date.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of curd initiation, influenced by transplanting dates, is a crucial factor affecting yield and maturity. Ara et al (2009) [1] reported significant effects on vegetative growth parameters, such as plant height, number of leaves, whole plant weight, marketable curd weight, and yield, based on both the variety and planting date.…”
Section: Introductionmentioning
confidence: 99%